Effect of algorithm parameters in development of spiral tool path for machining of 2.5D star-shaped pockets. (4th July 2019) - Patel, Divyangkumar D.; Lalwani, Devdas I.
2.5D pocket milling is extensively used in aerospace, shipyard, automobile, dies and moulds industries. In machining of 2.5D pockets, directional parallel tool-path and contour parallel tool-path are widely used. However, these tool paths significantly limit the machining efficiency. In the present work, an attempt has been made to generate a spiral tool path for machining of 2.5D star-shaped pocket for improving machining efficiency. The successful generation of spiral tool path depends on various algorithm parameters such as mesh size, permissible error and number of degree-steps. The effect of these parameters on spiral tool path generation is discussed and the best values are reported. The spiral tool path is developed using second order elliptic partial differential equation (PDE) and it is free from sharp corners inside the pocket region. Further, the implementation of proposed method is presented on complex non-star-shaped polygon, pocket bounded by free-form curve and pocket with island.